Familial idiopathic short stature and beyond: a case-report of a novel heterozygous NPR2 mutation. - Ylenia Giorgianni; Cecilia Lugarà; Francesca Franchina; Mariella Valenzise; Giorgia Pepe; Tommaso Aversa (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche, 2024)
Background: NPR2 gene encodes for B-type natriuretic peptide receptor (NPR-B), a positive regulator of the growth plate. Recently, heterozygous NPR2 mutations were reported in 2–6% cases of idiopathic short stature (ISS) and 13.6% of familial ISS.